Electrochemiluminescence Immunosensor Based on Functionalized Graphene/Fe3O4‐Au Magnetic Capture Probes for Ultrasensitive Detection of Tetrodotoxin. Issue 9 (8th June 2017) - Shang, Fang; Liu, Yuan; Wang, Sui; Hu, Yufang; Guo, Zhiyong
Abstract: An ultrasensitive electrochemiluminescence (ECL) immunosensor for the detection of tetrodotoxin (TTX) is proposed, which are composed of the branched poly‐(ethylenimine) (BPEI) functionalized graphene (BGNs)/Fe3 O4 ‐Au magnetic capture probes and luminol‐capped gold nanocomposites (luminol‐AuNPs) as the signal tag. Herein, a typical sandwich immunecomplex was constructed on the glassy carbon electrode. The BGNs/Fe3 O4 ‐Au hybrids could efficiently conjugate primary antibody via the Au−S chemical bonds or Au−N chemical bonds and rapidly separate under external magnetic field. The introduction of BPEI to GO could enhance the luminol‐ECL intensity. Meanwhile, the multifunctional nanocomposites have been proved with good water‐solubility, excellent electron transfer, outstanding stability, etc. The luminescent luminol‐AuNPs, a high efficient electrochemiluminescence marker, can be assembled on the second antibody, which can produce the ECL signal to achieve the determination of TTX. This proposed ECL immunosensor with a linear range from 0.01–100 ng/mL can be applied in the detection of TTX in real samples with satisfactory results. Abstract :